Amelioration of Waves and Micro-vibrations by Micro-buckling in Open Celled Foam. Issue 1 (January 2017) - Balch, Samuel P.; Lakes, Roderic S.
Open cell polymer foam exhibits both an intrinsic micro-vibration frequency and a cut off frequency associated with resonance of the cell ribs. Compression of the foam causes regions of local buckling of ribs. Incipient buckling gives rise to negative stiffness and enhanced amelioration of waves. Transmitted wave amplitude is reduced by compression below and near the cut off frequency.